AI versus Human Content Creation on Instagram: Engagement Outcomes and Consumer Perceptions - Fleseriu, Cristina; Fron, Mara Ilinca (Oeconomica Jadertina, 2025)
The study examines the comparative performance of human- and AI-generated content on Instagram, evaluating both engagement metrics and consumer preferences. The aim is to identify whether AI can match or exceed human content creation in terms of reach, interaction, and perceived quality. A within-subjects field experiment was conducted on an existing Instagram account with 770 followers. Twenty-four single-image culinary posts (12 human-created, 12 AI-generated) were published in alternating order. Engagement data were collected via Instagram Insights and analyzed using the Mann-Whitney U test. Two Instagram Story surveys were conducted to identify which post elements (image, caption, recipe) most influenced engagement. Results showed that AI generated content has the potential to generate similar outcomes in terms of likes, comments, shares, saves, reach, impressions, engagement rate, or engagement score. Human content generated more comments and hashtag impressions, while AI content achieved greater profile visits and higher reach among non-followers. Survey findings indicated that visuals were the most important driver of engagement (64%), followed by recipe/information (26%) and captions (10%). Consumers preferred human visuals and recipes, but AI captions were more appealing. These results suggest complementary strengths, with implications for hybrid content strategies. The study was limited to a single Instagram account in the culinary niche, using static image posts. Results may not be generalized to other industries, platforms, or content formats. Potential platform effects, such as shadow banning, and limitations of the AI tool in generating certain dishes may also have influenced outcomes. Future research should test across industries, platforms, and content formats to explore long-term impacts of AI in content creation.